Can Inhibin B Reflect Ovarian Reserve of Healthy Reproductive Age Women Effectively? - Wen, Jingyi; Huang, Kecheng; Du, Xiaofang; Zhang, Hanwang; Ding, Ting; Zhang, Cuilian; Ma, Wenmin; Zhong, Ying; Qu, Wenyu; Liu, Yi; Li, Zhiying; Deng, Song; et al. (Frontiers in Endocrinology, 2021)
Objective The reference range and potential value of inhibin B are still unclear and controversial. This study aimed to define the variation trend of inhibin B in healthy women with age and explore its value in the reflection of ovarian reserve. Methods A total of 2524 healthy reproductive age women from eight medical institutes nationwide were recruited. The variation tendency of inhibin B with age was primarily established in the first group of 948 women and validated in another 605. We evaluated the relationship between inhibin B and classic ovarian reserve and function markers. The potency of inhibin B in predicting AFC <5-7 was also estimated and compared with FSH. Results The nomogram showed that serum levels of inhibin B rapidly decreased after the age of 40. Inhibin B was positively correlated with AMH (R = 0.57, P < 0.001), AFC (R = 0.34, P < 0.001) and testosterone (R = 0.10, P = 0.002), and negatively correlated with FSH (R = -0.41, P < 0.001) and LH (R = -0.20, P < 0.001) and FSH/LH (R=-0.18, P < 0.001), while no correlation was found with PRL. Unexpectedly, Inhibin B (AUC = 0.74, P < 0.001 for the establishment population; AUC = 0.78, P < 0.001 for the validation population) had a slightly higher value than FSH (AUC = 0.71, P < 0.001 for the establishment population; AUC = 0.72, P < 0.001 for the validation population) in diagnosing AFC <5-7. Conclusions For healthy reproductive age women, the decline of inhibin B can reflect decreased ovarian reserve effectively, having a good consistency with AMH and AFC. More importantly, inhibin B had an advantage in predicting AFC <5-7 compared with FSH, which suggested the potential of inhibin B in predicting ovarian response. These results will be helpful to the clinical application of inhibin B in the evaluation of female ovarian reserve and the assessment of their reproductive capacity. Trial registration: http://clinicaltrials.gov; NCT02294500.